Ensino de topografias variadas do mando por informação “Quando?” em crianças com autismo - Brassolatti, Isabella Marino (Universidade Federal de São Carlos, 2022)
Recent studies have been developing procedures for teaching complex verbal operants to children with autism spectrum disorders (ASD), such as mands for information. However, the literature evaluating procedures for the acquisition of the mand “When?”, which can be evoked by a variety of stimuli correlated with delayed access to reinforcers, is still scarce. The present study aimed to replicate and extend the study by Landa, Hansen and Shillingsburg (2017), using the same experimental task to teach children with autism the mand for information “When?”, including a new type of trial and teaching of specific topographies (names of items) varied from this type of mand. Three boys with autism participated in the study and were exposed to experimental trials in which, after issuing a mand for an item highly preferred by the participant (e.g. “Can I play with the tablet?”), access to the item was denied by the experimenter. (e.g., “Not now”), with the aim of creating motivation for issuing the mand based on the information in question. After going through the Baseline and Training conditions, the three participants learned the mand for information topographies taught in a few teaching sessions (from eight to eleven), which were issued only during the Establishment Operation Present (OEP) type trials, and not during the other types of control trials (Establishment Operation Absent – OEA and free access – AL, the latter being inserted only for two of the three participants). Two participants showed variability in the independent responses presented. However, for two participants, it was necessary to provide tips for issuing mands for itens, which significantly influenced the teaching of the skill.
Teaching varied mands for information using "When?" to children with autism
Keywords: Crianças com autismo; Operações motivacionais; Mando por informação; Comportamento verbal; Children with autism; Motivating operations; Mands for information; Verbal behavior; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO